GENDER-ROLE IDENTITY AMONG JORDANIAN MALE NURSING STUDENTS: A DESCRIPTIVE STUDY - Al-Zein, Hanan J.; Al-Khawaldeh, Omar A. (European Scientific Journal, ESJ, 2015)
The objectives of the study were to describe the reasons for choosing nursing to study, gender role classification, and gender-role characteristics according to Bem sex-role inventory among male Jordanian nursing students recruited from two nursing schools in Jordan. A cross-sectional descriptive quantitative study was conducted using a self-administrated questionnaire. The questionnaire consists of demographic information and Bem-sex role inventory. The data was analyzed with descriptive statistics (means and standard deviations. Results revealed that the highest reported reason for choosing nursing to study was “I like the profession” (36.9 %) and the lowest reported reason was “The only specialty I got approval at the University” 3.3%. Results revealed that 43.44% of students were found to be masculine, 45.08% androgyny, 9.02% undifferentiated, and 2.46% were feminine. Results revealed also that nursing students’ masculine subscale had the higher average score (5.58) out of 7, followed that of the neutral subscale (5.25) and the feminine subscale (4.73). The study suggests that modification of the policies for recruitment of nursing students at the nursing schools in Jordan is needed to meet the gender- role requirements of the nursing profession to enhance male nurses’ retention and promotion in nursing.